Internal Carotid Dissection as the Cause of Stroke in Childhood. (29th June 2021) - Cinelli, Giulia; Loizzo, Vitaliana; Montanari, Lisa; Filareto, Ilaria; Caramaschi, Elisa; Predieri, Barbara; Iughetti, Lorenzo
Abstract : Internal carotid artery (ICA) dissection is a cause of stroke, but it is often underdiagnosed in children. ICAs' risk factors and pathogenic mechanisms are poorly understood, and the treatment is still empirical. We report the case of a previously healthy 9-year-old girl who presented with involuntary hypertonic closure of the right hand associated with transient difficulty for both fine movements of the right arm and speech. She had a history of minor cervical trauma occurring 20 days prior to our observation without other associated risk factors. Magnetic resonance imaging and magnetic resonance angiography showed ischemic lesions due to the left ICA dissection. Treatment with both acetylsalicylic acid and levetiracetam allowed recanalization of the ICA associated with the resolution of clinical signs. Our clinical case suggests that the ICA dissection must be suspected early whenever a child manifests mild neurologic deficits after a cervical trauma, especially if they are associated with headache and/or cervical pain. Moreover, the management of ICA dissection must be improved.